Extração e pirólise do óleo de girassol (Helianthus annus l.) visando a produção de biocombustíveis - Correia, Iara Michelle Silva (2009)
Nowadays, the growing environmental worry leads research the focus the application of alternative materials from renewable resources on the industrial process. The most common vegetable oil extractant using around the world is the hexane, a petroleum derived, toxic and flammable. Based on this fact, the goal of this work was to test vegetable oil extractions from sunflower seeds cultivated on the Rio Grande do Norte State using two extraction process, the mechanical expelling and solvent extraction, this one using hexane and ethanol as a alternative solvent. The solvent extractions were carried out in the Soxhlet extractor in three different extraction times (4, 6, and 8 hours). The effect of solvent and extraction time was evaluated. The mechanical extraction was carried out in a expeller and the sunflower oil obtained was characterized by its physical-chemical properties and compared with sunflower refinery oil. Furthermore this work also explored the pyrolysis reaction carried out by thermogravimetry measurement as alternative route to obtain biofuel. For this purpose the oil samples were heated to ambient temperature until 900°C in heating rate of 5, 10, 20ºC min-1 with the objective evaluated the kinetics parameters such activation energy and isoconversion. The TG/DTG curves show the thermal profile decomposition of triglycerides. The curves also showed that antioxidant presents on the refinery oil not influence on the thermal stability of sunflower oil. The total yield of the extraction s process with hexane and ethanol solvent were compared, and the results indicated that the extraction with ethanol were more efficient. The pyrolysis reaction results indicated that the use of unpurified oil required less energy to obtain the bio-oil